2014
DOI: 10.3402/gha.v7.23611
|View full text |Cite
|
Sign up to set email alerts
|

The workforce for health in a globalized context – global shortages and international migration

Abstract: The ‘crisis in human resources’ in the health sector has been described as one of the most pressing global health issues of our time. The World Health Organization (WHO) estimates that the world faces a global shortage of almost 4.3 million doctors, midwives, nurses, and other healthcare professionals. A global undersupply of these threatens the quality and sustainability of health systems worldwide. This undersupply is concurrent with globalization and the resulting liberalization of markets, which allow heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
246
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(260 citation statements)
references
References 14 publications
5
246
0
9
Order By: Relevance
“…This finding may be due the low ratio of health worker to population in most developing countries (Aluttis, Bishaw, & Frank, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…This finding may be due the low ratio of health worker to population in most developing countries (Aluttis, Bishaw, & Frank, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…2 Its primary purpose is to protect vulnerable source countries whose health systems are undermined through losing scarce health professionals to wealthy destination countries. 3,4 Recent articles have questioned the relevance and effectiveness of the Code, 5,6 given lack of awareness or perhaps lack of concern about the requirements of the Code in some destination countries; and a lack of reporting by most source countries. 4,5 It has been suggested that the voluntary nature of the Code means that it has limited impact on destination country recruitment practices.…”
Section: What Is the Who Global Code?mentioning
confidence: 99%
“…[2] Health worker shortages affect a health system's ability to offer universal access to good quality care. There is evidence that health worker migration has adverse effects on population health outcomes, [3,4] and density of health workers is positively correlated with maternal, child, and infant survival. [5] Nurses currently represent 60%-80% of the world's health-care workforce and they provide 90% of healthcare worldwide.…”
Section: Introductionmentioning
confidence: 99%